2018
DOI: 10.1158/1541-7786.mcr-17-0594
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Response to Neoadjuvant Chemotherapy in High-Grade Serous Ovarian Carcinoma

Abstract: While high-grade serous ovarian carcinoma (HGSOC) is the most common histologic subtype of ovarian cancer, significant tumor heterogeneity exists. In addition, chemotherapy induces changes in gene expression and alters the mutational profile. To evaluate the notion that patients with HGSOC could be better classified for optimal treatment based on gene expression, we compared genetic variants [by DNA next-generation sequencing (NGS) using a 50 gene Ion Torrent panel] and gene expression (using the NanoString Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 44 publications
2
38
1
Order By: Relevance
“…Genome doubling was calculated based on the mean ploidy of the sample. If the mean ploidy reported by FACETS was greater than 3, the sample was termed to have undergone genome doubling [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genome doubling was calculated based on the mean ploidy of the sample. If the mean ploidy reported by FACETS was greater than 3, the sample was termed to have undergone genome doubling [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although HGSOC is the most common histological subtype of ovarian cancer, there is a considerable amount of tumor heterogeneity (Arend et al, 2018), thus underscoring the need for comprehensive characterization of the molecular subtypes of this lethal disease. Previous studies have shown that somatic mutations (Wiegand et al, 2010), genetic (Gates et al, 2010) and environmental risk factors (Goode et al, 2010), and the clinical response rates to platinum- or taxane-based therapy (Sugiyama et al, 2000) vary considerably among the HGSOC molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these BRCA1/2 reversion mutations could be detected by ctDNA sequencing analysis in the patients who received platinum and/or PARP inhibitors [116]. Rebecca et al [117] compared the genetic variants of a panel of 50 genes between tumor and ctDNA among 20 patients diagnosed with the high-grade ovarian carcinoma during neoadjuvant chemotherapy (NACT). Notably, 38 genetic variants out of six genes (TP53, KIT, KDR, KRAS, PIK3CA, and PTEN) were identified in tumors pre-NACT, while 59 variants out of 19 genes were detected in the ctDNA.…”
Section: Egf Receptormentioning
confidence: 99%
“…Most of the mutations found in ctDNA were not present in tumor resulting from the amplifying of ctDNA. Besides, the heterogeneity in the tumor can be detected in ctDNA, in contrast with tumor tissue [117].…”
Section: Egf Receptormentioning
confidence: 99%